Effects of silane coupling agent level and extraction treatment on the properties of UF-bonded reed and wheat straw particleboards - Han, Guangping; Umemura, Kenji; Wong, Ee Ding; Zhang, Min; Kawai, Shuichi (Springer, 2001)
Urea formaldehyde resin bonded reed and wheat particleboards with a density of 0.7g/cm3 were manufactured from two types of particle: fine and coarse particles. The effects of the silane coupling agent (SCA) level and ethanol-benzene (EB) treatment on the board properties were examined. For SCA, epoxide silane (SiEP) and amino silane (SiNH) were used for reed and wheat particles, respectively. The results are summarized as follows. (1) For both reed and wheat boards, the internal bond (IB) strength and thickness swelling (TS) were significantly improved at up to 5% SCA content, but the effectiveness of treatment kept constant at above 5%. (2) The level of SCA had little effect on the bending strength, especially for the boards composed of coarse particles. (3) EB treatment upgraded both the IB and TS of wheat board significantly. (4) SiEP incorporation improved the IB and TS of reed board significantly, whereas EB treatment was more effective for wheat board. (5) The dimensional stability of both reed and wheat boards under varying humidity could be improved by increasing the level of SCA and by EB treatment. EB treatment was more effective than SCA addition.